Pengaruh Harga dan Kualitas Produk terhadap Kepuasan Pelanggan Kafe Immune Kota Palopo - Yuda Satria Nugraha; Wulan Guritno; Adri Kalatiku; Uun Lestari; Nurjannah Nurjannah (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
This study aims to determine the effect of price and product quality on customer satisfaction. The research population is all customers at the Immune Cafe in Palopo City. With the incidental sampling technique, a sample of 30 people was selected. This study uses a quantitative approach and inferential statistical analysis. The data used consists of primary data and secondary data. Data collection was carried out by providing instruments in the form of questionnaires to respondents. The data analysis model used is multiple linear regression analysis with two independent variables, namely price and product quality, and one dependent variable, namely customer satisfaction. The results showed that price and product quality simultaneously had a positive and significant effect on customer satisfaction. As for partially, price has no significant effect on customer satisfaction, while product quality has a positive and significant effect on customer satisfaction. This shows that the product quality variable is more dominant in influencing customer satisfaction than the price variable